2019
DOI: 10.1108/gm-07-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

In the mother’s shadow: exploring power dynamics in family business succession

Abstract: Purpose This paper aims to investigate and explain the power dynamics involving the mother (as the founder) and the daughter (as the successor) during the business transmission process. Design/methodology/approach This qualitative research was conducted on a sample of Italian family SMEs. The adopted approach is consistent with the narration paradigm, where the biographical features of the participant are investigated to highlight the culture, value systems and other background features. Findings This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…As the number of women-owned family business increases, research on the women-led family business's succession process also emerges. Ramadani et al (2017b) found that children's gender does not matter in the Gender issues in family business research 2019) 's finding suggested that attachment to power has no gender (Ferrari, 2019). Nevertheless, myriad issues remain untapped or unresolved in this research line.…”
Section: Women's Challenges and Opportunities In The Family Businessmentioning
confidence: 94%
“…As the number of women-owned family business increases, research on the women-led family business's succession process also emerges. Ramadani et al (2017b) found that children's gender does not matter in the Gender issues in family business research 2019) 's finding suggested that attachment to power has no gender (Ferrari, 2019). Nevertheless, myriad issues remain untapped or unresolved in this research line.…”
Section: Women's Challenges and Opportunities In The Family Businessmentioning
confidence: 94%
“…As the number of the women-owned family business is increasing, researches on the succession process in the women-led family business also emerge. Ramadani, Dana, et al (2017) found that children's gender does not matter in the succession process but the children's interest, whereas Ferrari (2019)'s finding suggested that attachment to power has no gender (Ferrari, 2019).…”
Section: Women's Challenges and Opportunities In The Family Businessmentioning
confidence: 99%
“…Recently, scientists in this line of research seemed to acquire a rising interest in the topic regarding the challenges of daughters in the succession process. Findings of more recent studies continued asserting the massive difficulties that daughters experience during the succession process (Ahrens et al, 2015;Byrne et al, 2019;Ferrari, 2019;Gherardi & Perrotta, 2016;Mussolino, Cicellin, Iacono, Consiglio, & Martinez, 2019;Ramadani, Dana, Sadiku-Dushi, Ratten, & Welsh, 2017). However, the research approach in this line of research has been recently diversified.…”
Section: Women's Challenges and Opportunities In The Family Businessmentioning
confidence: 99%
“…These inconclusive results might be explained by unobserved moderating factors such as the family CEO's gender, as alternate mechanisms work in male-led versus female-led organizations (Elsaid and Ursel, 2011;Zhang and Qu, 2016). Despite the increasing presence and importance of women in family businesses (Nelson and Constantinidis, 2017;Kubí cek and Machek, 2019), the research on this topic is still fragmented and mostly conceptual, especially on women involved in the business as a family CEO (Campopiano et al, 2017;Ferrari, 2019). As female CEOs are likely to provide different solutions to management and broader business problems (Koffi et al, 2014), gender differences can also influence SP in family firms.…”
Section: Gendermentioning
confidence: 99%
“…In family business research, it is only recently that gender issues have gained more attention (Ferrari, 2019;Kubí cek and Machek, 2019). As differences between female and male CEOs can vest themselves in how the business is organized, the family CEO's gender may have implications for the business within the context of leadership succession (Kubí cek and Machek, 2019).…”
Section: Introductionmentioning
confidence: 99%